The relation of the physical body to the mental body - Baird, Nellie Wilhelmina (My University, 1905)
Introduction: When we consider physical culture in the various states of development, we find that it runs parallel with the intellectual and ethical efforts of mankind. The latter were caused, to a great extent, by the material wants of the individual. To the pre -historic human being, the struggle for existence was a severe teacher of physical training. Man, in his primitive state soon found that he who could handle the largest club and throw the heaviest stone had the best prospects for life. The wild woods were his gymnasium; his competitive games were battles for life, either with the beasts of the woods or with the human foes of his tribe. History tells us of but one people in whom physical culture manifested itself, as it were, as the living idea of beauty. These were the ancient Greeks. But only for a comparatively short time did the Greeks stand on this unparalleled high pedestal of physical culture. In proportion to their intellectual and political decline physical culture returned again to little better than barbarism, proving thus that mind and body will always ascend or descend together. Though the aspiration for the noble and beautiful had proved the most successful teacher of physical culture, the Romans dismissed him and engaged Master War again as their ideal teacher. It is true he served them faithfully, but could not prevent the dawn fall of the Roman Empire, because the Roman mind soon degenerated and mighty Rome died of voluptuousness. In the Middle Ages chivalry became the bearer of physical training, but the people at large were "dumb -driven cattle". Europe fell victim to this piratical state. Rapacity, ambition, struggle for supremacy were the motives of its physical culture.
Citation: Baird, Nellie Wilhelmina. The relation of the physical body to the mental body. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Revival of Learning; Muscular Activity; Harvey and Blood Circulatuon; Theses